2010
DOI: 10.1095/biolreprod.109.079251
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Is Not Involved in Preovulatory Down-Regulation of CYP11A1, HSD3B1, and CYP19A1 in Bovine Follicles but May Have a Role in Permanent Silencing of CYP19A1 in Large Granulosa Lutein Cells1

Abstract: The luteinizing hormone-induced morphological and physiological reorganization of the bovine follicle is preceded by a profound and well-orchestrated modulation of gene expression. In the present study, the cell type-specific methylation profiles of CYP11A1, HSD3B1, and CYP19A1, genes that encode key enzymes of steroid hormone biosynthesis, were analyzed to elucidate whether epigenetic parameters such as DNA methylation might be involved in gene regulation during luteinization. Transcript abundance and DNA met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 42 publications
(67 reference statements)
2
19
1
Order By: Relevance
“…It has been established that in response to LH surge, CYP19A1 expression gets down regulated and may even be absent post ovulation [85][87]. However, others [36] and we (in the present study) have observed CYP19A1 expression in the non-pregnant CL.…”
Section: Discussioncontrasting
confidence: 62%
“…It has been established that in response to LH surge, CYP19A1 expression gets down regulated and may even be absent post ovulation [85][87]. However, others [36] and we (in the present study) have observed CYP19A1 expression in the non-pregnant CL.…”
Section: Discussioncontrasting
confidence: 62%
“…Modifications in the methylation state of the steroidogenic enzyme genes P450scc and 3β-HSD have been previously described (Vanselow et al, 2010;Zhang and Ho, 2011). In addition, changes in the DNA methylation of the P450(17α) gene were observed during cellular senescence in bovine adrenocortical cells.…”
Section: Article In Pressmentioning
confidence: 82%
“…In the past 15 years, there has been an explosion in the “omics” world, including transcriptomics, proteomics (115, 116), metabolomics (117), and epigenomics (118). Microarrays have been used extensively to study folliculogenesis in isolated ovaries (119), follicles (120), oocytes (121), and granulosa or theca cells (122) and in untreated (123, 124) or treated cell lines (125127).…”
Section: Emerging Opportunitiesmentioning
confidence: 99%